The importance of interactions in supporting online study - Le, Ngoc Quyet; Sankaran, Shankar (Technium Social Sciences Journal, 2023)
The social distancing rules during the COVID-19 pandemic have inadvertently changed the activities of teaching and learning- with an unprecedented push to online courses. Educational institutions in developed countries have quickly adapted to the situation by developing their digital platforms to support e-learning. Whereas those in developing countries, particularly Vietnam, found it challenging to respond to the significant increase in online instruction because of lack of equipment and technology gap. This paper aims to examine a blending approach which combines visual technologies and social interactions to support full-time remote education. Qualitative method was employed with the use of thematic analysis to examine respondents’ perspectives of their daily online learning. Data was collected through semi-structured interviews of 05 lecturers and 10 undergraduate students in site construction management discipline as they are among groups experiencing seriously negative effects on quality of knowledge exchange which requires amount of time practice on-site or field-laboratory. Activity Theory was employed to guide the data analysis. Four main themes were found in related to “using interactive tools”, “developing a learning support community”, “defining responsibilities of educators and students” and “governing activities of educators and students” to meet learning objectives within online courses.